2011
DOI: 10.1016/j.jvs.2011.01.064
|View full text |Cite
|
Sign up to set email alerts
|

A comparison between one- and two-stage brachiobasilic arteriovenous fistulas

Abstract: Primary and secondary patency at 1 and 2 years as well as functional patency is improved with the two-stage BBAVF when compared with the one-stage procedure. Lower primary failure rates prior to dialysis with the two-stage procedure approached, but did not reach statistical significance. While reasons for these finding are unclear, certain technical aspects of the procedure may play a role.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 18 publications
(28 reference statements)
1
32
1
Order By: Relevance
“…15 The eight remaining studies that reported on 882 patients met the inclusion criteria and consisted of one randomized controlled trial (RCT) 3 and seven retrospective, observational, cohort studies. 4,5,[16][17][18][19][20] Study baseline characteristics are summarized in Table I. Five of the studies were from the United States, with one each from the United Kingdom, Turkey, and Egypt.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…15 The eight remaining studies that reported on 882 patients met the inclusion criteria and consisted of one randomized controlled trial (RCT) 3 and seven retrospective, observational, cohort studies. 4,5,[16][17][18][19][20] Study baseline characteristics are summarized in Table I. Five of the studies were from the United States, with one each from the United Kingdom, Turkey, and Egypt.…”
Section: Resultsmentioning
confidence: 99%
“…The two-stage approach requires two separate procedures but may allow easier superficialization of an "arterialized vein" and avoids a more invasive procedure if early failure is detected. A number of studies have been published comparing vessel patency and functional patency rates of both approaches, with some suggestion of improved patency with the twostage technique [3][4][5] ; however, there is no clear indication of which approach is best. 6 In the present study, we conducted a systematic review and meta-analysis of studies that compared one-stage vs two-stage BVT to determine which approach results in lower failure rates and improved primary and secondary patency rates.…”
mentioning
confidence: 99%
“…To date, limited and conflicting data exist regarding primary failure and the patency rates of one-stage and two-stage procedures. [4][5][6][7][8][9][10][11][12] Each procedure has advantages and disadvantages. The one-stage procedure offers the benefits of a single operation with earlier functional patency and possible shorter duration with a central venous catheter.…”
mentioning
confidence: 99%
“…In accordance with local practice, BVs were deemed suitable for AVFs if >2.5 mm in diameter at elbow level using a proximal occluding cuff and, in accordance with established evidence and recent publications, 20,21 if they were compressible (not thrombosed) on vascular/clinical assessment. Venography of the assessed limb and central vein was also done upon clinician discretion if indicated by extensive previous use of central veins for venous access to exclude a central venous stenosis.…”
Section: Methodsmentioning
confidence: 87%